The need for financial education in the face of the social media and cryptocurrency phenomenon - Martin Gomez, Sonia; Bartolome Muñoz de Luna, Angel (Business, Management and Economics Engineering, 2025)
Purpose – is to provide evidence of how social networks act as an indispensable channel in the cryptocurrency phenomenon and its public perception, analysing the context in which it occurs, as well as the patterns followed and the most commonly used channels.Research methodology – this article explores and provides evidence on the relationship between cryptocurrencies and social networks through the use of digital social listening tools, exploring data retrieved from the most prominent social networks, as well as websites, forums and blogs.Findings – the urgent need to provide an adequate level of financial education in the digital economy. Research limitations – the study should be carried out by age segments to assess whether it is only a problem of the younger population, which are the habitual users of social networks. Practical implications – the cryptocurrency user or investor is aware of the existing risks associated with cryptocurrencies, especially among the young population, without underestimating the influence that social networks have had and continue to have on the perception and acceptance of digital currencies, and even on their popularity.Originality/Value – investing in cryptocurrencies requires social responsibility on the part of institutions, demanding adequate legislation and financial training for potential investors.